2012
DOI: 10.1530/rep-12-0188
|View full text |Cite
|
Sign up to set email alerts
|

Alteration in localization of steroid hormone receptors and coregulatory proteins in follicles from cows with induced ovarian follicular cysts

Abstract: Cystic ovarian disease (COD) is an important cause of infertility in cattle. The altered follicular dynamics and cellular differentiation observed in COD may be mediated through a disruption of the expression of steroid receptors and their associated transcriptional cofactors. The aim of this study was to determine the protein expression profiles of ESR1, ESR2, PGR, AR, NCOA3, NCOR2, and PHB2 (REA) in ovarian follicles in an experimental model of COD induced by the administration of ACTH. Ovaries were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 88 publications
(105 reference statements)
1
28
0
3
Order By: Relevance
“…In addition, studies on cows with COD induced by the administration of ACTH have evidenced changes only in the expression of ESR2 in cystic follicles compared with control follicles, partially coinciding with the findings in animals with spontaneous disease , Alfaro et al 2012. Studies have also demonstrated an increase in ESR1 expression in animals with spontaneous COD and not in the experimental model, differences that are probably due to the persistence time of the cysts (Salvetti et al 2012).…”
Section: R253mentioning
confidence: 54%
See 4 more Smart Citations
“…In addition, studies on cows with COD induced by the administration of ACTH have evidenced changes only in the expression of ESR2 in cystic follicles compared with control follicles, partially coinciding with the findings in animals with spontaneous disease , Alfaro et al 2012. Studies have also demonstrated an increase in ESR1 expression in animals with spontaneous COD and not in the experimental model, differences that are probably due to the persistence time of the cysts (Salvetti et al 2012).…”
Section: R253mentioning
confidence: 54%
“…Studies have also demonstrated an increase in ESR1 expression in animals with spontaneous COD and not in the experimental model, differences that are probably due to the persistence time of the cysts (Salvetti et al 2012). Other authors have found analogous modifications in the expression of ESR2 in cysts from women with polycystic ovarian syndrome related to normal-size follicles (Jakimiuk et al 2002) and in prenatal testosterone-treated sheep characterized by an abnormal follicular persistence ).…”
Section: R253mentioning
confidence: 91%
See 3 more Smart Citations